2012
DOI: 10.1071/fp12051
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant promoter methylation occurred from multicopy transgene and SU(VAR)3 - 9 homolog 9 (SUVH9) gene in transgenic Nicotiana benthamiana

Abstract: The chemical modification of DNA by methylation is a heritable trait and can be subsequently reversed without altering the original DNA sequence. Methylation can reduce or silence gene expression and is a component of a host’s defence response to foreign nucleic acids. In our study, we employed a plant transformation strategy using Nicotiana benthamiana Domin to study the heritable stability of the introduced transgenes. Through the introduction of the cauliflower mosaic virus (CaMV) 35S promoter and the green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The main advantage of constitutive promoters is that they continuously express the gene in all parts of the plant. However, it was demonstrated that spontaneous transgene-silencing phenomena are caused by methylation of the CaMV 35S promoter during transgenic plant growth [74,75]. In addition, there is an increased chance of homology dependent gene silencing (HDGS) occurring.…”
Section: Improvement Of Rice Expression Systemmentioning
confidence: 99%
“…The main advantage of constitutive promoters is that they continuously express the gene in all parts of the plant. However, it was demonstrated that spontaneous transgene-silencing phenomena are caused by methylation of the CaMV 35S promoter during transgenic plant growth [74,75]. In addition, there is an increased chance of homology dependent gene silencing (HDGS) occurring.…”
Section: Improvement Of Rice Expression Systemmentioning
confidence: 99%
“…The main advantage of constitutive promoters is the constant gene expression in all parts of the plant. However, constitutive promoters have a low expression level and often undergo silencing as a result of methylation during transgenic plant growth [107]. Methods based on the use of inducible promoters are activated only under special conditions, and tissue-specific promoters working in certain plant organs became more widely used with the development of biotechnology.…”
Section: Introductionmentioning
confidence: 99%